(untitled) (Faridpur Medical College Journal, 2015)
Ceramic factory workers are potentially at risk to develop occupational respiratory diseases due to chronic inhalation of dust particles generated in the ceramic factory. A cross-sectional descriptive study was carried out to assess the respiratory and other health problems among the workers of Mirpur Ceramic Works Limited, Dhaka, Bangladesh during the period of April to June, 2011. Among 200 participants, 132 (66%) were males and 68 (34%) were females. Less than one-third of the workers were habituated to use personal protective equipments (PPE), while more than two-third were not habituated. Nearly half (45.5%) of the workers were suffering from at least one respiratory problem and of them 86.8% (P = 0.001) had problems after joining the factory. Of the respiratory sufferers 27% had chronic bronchitis, 20% bronchial asthma, 1% pulmonary tuberculosis, and 0.5% had silicosis. A significant numbers (60.5%) of workers were suffering from other health problems along with or without respiratory problems, in terms of musculoskeletal pain, back pain, headache, dermatitis, anaemia and fever. The prevalence of respiratory problems was significantly higher among non-users of PPE than PPE users (P = 0.006), and it was found to be higher with the increased of job duration. The study showed the notable higher prevalence of respiratory problems among the workers exposed to ceramic dust, although the other potential environmental confounding factors could not be ruled out in the analysis. Obligatory use of PPE by all workers and health education to increase awareness among the workers might have role to reduce the prevalence. Faridpur Med. Coll. J. 2014;9(1): 19-23